P-chiral organophosphorus compounds: synthesis, mechanism, and applications - Chandanshive, Amol C.; Chikkali, Samir H. (Chemistry-an Asian Journal, 2026)
The enantioselective synthesis of P-stereogenic compounds has emerged as a central focus in modern asymmetric catalysis, driven by their pivotal roles as ligands (Ls), organocatalysts, and bioactive molecules. Over the past decade, significant advances have been made in developing catalytic strategies that enable precise control over phosphorus stereochemistry, expanding both the structural diversity and synthetic utility of these scaffolds. This review highlights recent progress in two key areas: direct P-C bond formation and desymmetrization. P-C bond-forming approaches include cross-coupling reactions of secondary phosphines or their oxides with aryl, alkyl, or benzyl halides, as well as hydrophosphination of alkenes and alkynes. Desymmetrization strategies encompass nucleophilic substitution at P(V) centers, cyclization, C-H activation (CHA), phenolic -OH activation, and P-O alkylation/arylation. Mechanistic insights into these transformations have been discussed, along with the derivatization of P-chiral products and their applications in catalysis, L design, and bioactive molecule synthesis. This comprehensive overview shall serve as a valuable resource for researchers working in asymmetric organophosphorus chemistry.
Keywords: desymmetrization; Hydrophosphination; P-C cross coupling; P-chiral phosphines; phosphination